2013
DOI: 10.1016/j.rmed.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pirfenidone in idiopathic pulmonary fibrosis in clinical practice

Abstract: These results showed that pirfenidone was well-tolerated and had beneficial effects in patients with mild-to-severe and/or progressive IPF. The degree of disease progression prior to the initiation of pirfenidone therapy had an impact on the response to the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
73
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 16 publications
20
73
3
Order By: Relevance
“…Yearly FVC decline in the first year of treatment was 30 mL, which was even less than that obtained in a phase III trial (80-90 mL) (5). Recently, Okuda et al reported that the mean change in FVC during the 6-month period prior to therapy initiation was -188 mL, which improved to -19 mL during the 6-month period after the therapy (9). Meanwhile, in the present study, the yearly decline in FVC in the second and third years was 158 mL and 201 mL, respectively, and long-term pirfenidone treatment improved FVC in only a fraction of the cases.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Yearly FVC decline in the first year of treatment was 30 mL, which was even less than that obtained in a phase III trial (80-90 mL) (5). Recently, Okuda et al reported that the mean change in FVC during the 6-month period prior to therapy initiation was -188 mL, which improved to -19 mL during the 6-month period after the therapy (9). Meanwhile, in the present study, the yearly decline in FVC in the second and third years was 158 mL and 201 mL, respectively, and long-term pirfenidone treatment improved FVC in only a fraction of the cases.…”
Section: Discussioncontrasting
confidence: 41%
“…It is important to balance efficacy and adverse events in the clinical use of pirfenidone (9,12). In the present study, the most common dose of pirfenidone administered for the longest period of time was 1,800 mg/day among cases that continued pirfenidone treatment for two years or longer.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to long-term observational studies, a number of recent single-centre studies have been published reporting the efficacy and tolerability of pirfenidone in a real-world setting (table 3) [13][14][15][16][17][18][19][20]. Generally, these single-centre observational studies demonstrate that in daily clinical practice the tolerability of pirfenidone is comparable to the literature with a positive effect in terms of clinical efficacy in the majority of patients treated, particularly regarding disease stabilisation and prevention of pulmonary function decline.…”
Section: Single-centre Real-world Experience With Pirfenidonementioning
confidence: 99%
“…2011-2014: long-term and real-world experience in the treatment of IPF with pirfenidone Since the approval of pirfenidone in 2011 by the EMA, important data on the use of pirfenidone from clinical studies, long-term observational studies and real-world practice has been accumulated, demonstrating that pirfenidone significantly reduces forced vital capacity (FVC) decline and slows disease progression in IPF [22][23][24][25][26][27][28][29][30]. These longer term studies also showed that pirfenidone is generally well tolerated.…”
Section: Introductionmentioning
confidence: 99%